2016
DOI: 10.1016/j.jacc.2016.03.522
|View full text |Cite
|
Sign up to set email alerts
|

Early Intravenous Beta-Blockers in Patients With ST-Segment Elevation Myocardial Infarction Before Primary Percutaneous Coronary Intervention

Abstract: In a nonrestricted STEMI population, early intravenous metoprolol before PPCI was not associated with a reduction in infarct size. Metoprolol reduced the incidence of malignant arrhythmias in the acute phase and was not associated with an increase in adverse events. (Early-Beta blocker Administration before reperfusion primary PCI in patients with ST-elevation Myocardial Infarction [EARLY-BAMI]; EudraCT no: 2010-023394-19).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(93 citation statements)
references
References 23 publications
2
87
0
4
Order By: Relevance
“…Accordingly, in a large observational study (>44,000 patients), beta-blockers were not associated with mortality benefit in patients with prior MI or those without a history of AMI (23). Our observations support the argument that in the current clinical practice incremental survival benefits associated with use of beta-blockers may be smaller than benefits associated with use of the other 2 evidence-based preventive therapies (2325). …”
Section: Discussionsupporting
confidence: 84%
“…Accordingly, in a large observational study (>44,000 patients), beta-blockers were not associated with mortality benefit in patients with prior MI or those without a history of AMI (23). Our observations support the argument that in the current clinical practice incremental survival benefits associated with use of beta-blockers may be smaller than benefits associated with use of the other 2 evidence-based preventive therapies (2325). …”
Section: Discussionsupporting
confidence: 84%
“…In the reperfusion era, the COMMIT trial indicated that there was more developing cardiogenic shock per 1000 persons (5·0% vs. 3·9%; p<0.00001) allocated to metoprolol group, especially on days 0 and 19. In a Swedish nationwide observational study, the use of intravenous beta-blockers in STEMI patients without cardiogenic shock and cardiac arrest at presentation treated with primary PCI was associated with higher short-term mortality, lower LVEF at discharge, as well as a higher risk of in-hospital cardiogenic shock [14,15]. While recent meta-analysis concluded that early use of intravenous beta-blockers in STEMI patients presenting in Killip Class 1 or 2 was not associated with increase in the risk of cardiogenic shock in the current reperfusion era [11,12].…”
Section: Cardiogenic Shockmentioning
confidence: 99%
“…Global [13]. This beneficial effect on infarct size and LVEF; however, was not demonstrated in another similar designed study [14]. A recent metaanalysis of four trails only enrolled patients with confirmed STEMI with symptoms lasting less than 6 or less than 12 h concluded that intravenous beta-blockers in conjunction with PCI are associated with improved LVEF at 24 weeks in STEMI patients presenting in Killip Class 1 or 212.…”
Section: Infarct Size and Left Ventricular Ejection Fraction (Lvef)mentioning
confidence: 99%
“…This trial showed that early routine administration of IV metoprolol is not beneficial in reducing infarct size in patients with STEMI and primary PCI. 16 The Resuscitation Outcomes Consortium Amiodarone, Lidocaine, Placebo Study Antiarrhythmic drugs are usually used in out-of-hospital cardiac arrest (OHCA) with shock-refractory ventricular fibrillation (VF) or pulseless ventricular tachycardia (VT), although the benefits for survival of these therapies have not been MANO T et al…”
Section: Early-bamimentioning
confidence: 99%